2023
DOI: 10.54254/2753-7048/21/20230171
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of ChatGPT on the Learning Efficacy of Chinese College Students

Zhe Huang,
Man Wang,
Kun Yang

Abstract: With the popularization of online autonomous learning and the development of artificial intelligence, more and more students are starting to use ChatGPT to assist learning. Research gaps exist in understanding the intersection of artificial intelligence (AI), ChatGPT, and education. Based on reviewing relevant literature from domestic and foreign scholars, the authors combine quantitative and qualitative research methods to explore the relationship between the usage of ChatGPT and the learning efficacy of Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The study found significant associations between perceived intelligence, knowledge management, and personalization. Another study by Huang et al (2023) focused on Chinese college students and their use of ChatGPT. The study revealed that these students commonly rely on ChatGPT for information retrieval, coursework, and dissertation writing tasks.…”
Section: Overview Of Existing Researchmentioning
confidence: 99%
“…The study found significant associations between perceived intelligence, knowledge management, and personalization. Another study by Huang et al (2023) focused on Chinese college students and their use of ChatGPT. The study revealed that these students commonly rely on ChatGPT for information retrieval, coursework, and dissertation writing tasks.…”
Section: Overview Of Existing Researchmentioning
confidence: 99%